Pengaruh Media Sosial Terhadap Perkembangan Bahasa Gaul di Kalangan Remaja Gunungsitoli - Ndraha, Laurensia; Ginting, Destin Elsa Putri; Hura, Agus Kurniawan; Harefa, Noveri Amal Jaya (Indo-MathEdu Intellectuals Journal, 2024)
This study was conducted because of the growing use of slang among teenagers in Gunungsitoli. Its goal was to examine how social media influences the evolution of slang among these adolescents. Qualitative research was employed with a descriptive approach. The researcher acted as the main data collection instrument, aided by a camera, field notes, and writing materials. Data were gathered through observation and video recordings, and analysis involved data reduction, presentation, and drawing conclusions. The results revealed that numerous words from formal Indonesian have been transformed into widely used slang among teenagers, with notable positive and negative implications